Comparative analysis of growth patterns of Gannan Yak based on nonlinear models - Minghao Zhang; Tong Wang; Wondossen Ayalew; Zhilong Zhang; Xuelan Zhou; Qingbo Zheng; Min Chu; Guangyao Meng; Yongfu La; Chunnian Liang; Pengjia Bao; Ping Yan (Animal Biotechnology)
Body weight and withers height are critical indicators of growth in animals, influencing husbandry practices. In this study, we measured the body weight and withers height of Gannan yaks at different ages (0, 6, 18, 30, 42, 54, 66, and 78 months). Four nonlinear growth models (Logistic, Gompertz, von Bertalanffy, and Brody) were evaluated. The Brody model was identified as the best fit for both body weight and withers height. Females exhibited lower A values and higher K values than males, suggesting earlier onset of puberty. The absolute growth rate (AGR) for males ranged from 16.979 to 0.809 kg/month, while for females, it ranged from 7.202 to 0.588 kg/month. The relative growth rate (RGR) ranged from 74.00 to 0.18% for males and 27.12 to 0.25% for females. Regarding withers height, the AGR and RGR for males ranged from 3.749 to 0.0409 cm/month and 6.69 to 0.034%, respectively. For females, these values ranged from 3.765 to 0.0294 cm/month and 7.02 to 0.026%. Females exhibited fasterGA from birth to 78-months, while males had higher GA in withers height until 17 months, after which females surpassed malesA. Overall, males can achieve larger mature sizes, but females exhibited faster early GA.